Abortion, sexuality and bioethics in documents and Vatican Encyclicals - Gudiño Bessone, Pablo (Acta Bioethica, 2018)
The ways in which the Catholic Church is involved in discussions about contraception, abortion and assisted fertilization invite to observe the ability of the institution to assert its thought and doctrine into the emergence of new actors, practices and discourses. This essay has as objective a critical reading of a set of documents and Vatican encyclicals, starting with reading of Humanae Vitae of Paul VI. This in order to repair in the politicization of scientific and medical knowledge and the posing of sexuality and defense the legal right to life of fetuses/ embryos in the discursive field of Catholic personalist bioethics.